Injury Pattern of Blunt Trauma Cases Based on HDSS Sleman 2021 - Laksito, Aziz Pandu; WIraagni, Idha Arfianti; Widagdo, Hendro; Tri Artanti, Martiana Suciningtyas (Universitas Ahmad Dahlan, 2025)
Blunt trauma is a significant cause of death and injury worldwide. In Indonesia, traffic accidents are the leading cause of blunt trauma-related mortality and morbidity. Reports indicate that Yogyakarta alone experiences millions of accident cases, resulting in numerous injuries and fatalities. The incidence and severity of blunt trauma vary based on factors such as sex, age, lifestyle, environment, and access to healthcare. Blunt trauma, caused by strong impacts, falls, or physical assaults with blunt objects, does not involve skin penetration and includes contusions, abrasions, lacerations, and fractures. This study aims to identify the patterns of blunt trauma in the Sleman Regency in 2021 using the Health and Demographic Surveillance System (HDSS), a research tool for collecting longitudinal data on social changes to advance scientific knowledge in healthcare through population data analysis. The research employed both univariate and bivariate analyses. Univariate analysis used a cross-sectional observational design, while bivariate analysis utilized the chi-square test. In 2021, 315 blunt trauma injuries were reported, primarily from motorbike accidents (263 cases) and other land transportation incidents (52 cases). Most victims were men (55.9%), with the adult age group (19-59 years) experiencing the majority of injuries (285 cases). Lower extremities were most frequently injured (64% of cases), often resulting in loss of motor reflexes (10.7%). Contusions on the lower extremities were the most common injury type (42.3%). The study shows a higher incidence of blunt trauma among men, particularly adults. Injuries are primarily contusions in the lower extremities, indicating the need for targeted safety measures. Demographic factors such as education level and age group influence injury distribution, highlighting the importance of effective management strategies to mitigate severe functional impacts.